现代汉语结构助词“的”的隐现探究 ：以“人称代词＋（的）＋名词”结构为例 = The presence and absence of “de” in modern Chinese : a case study of the “personal pronoun + de + noun” construction - 梁佩雯 Neo, Peh Wen (2015)
“的”字这一虚词的隐现规律至今已有不少相关研究，而其中张敏（1998）所ᨀ出的论点受到许多学者的支持。张敏认为认知语言学能解释“的”字隐现的规律，但其讨论并没有ᨀ供详细的数据支持。本文将在大型语料库基础上，利用数据和统计对张敏的论点进行检验。本文将主要探讨“人称代词＋（的）＋名词”这一领属结构。因此本文设定了两种词表，分别为人称代词词表与名词词表，并调查这两者搭配时，“的”的隐现情况，即两者之间是否需要插入“的”。本文利用统计方法查看了多种可能影响“的”字隐现的因素，如人称代词及中心语的影响，音节，词汇的内部语义和认知差异，文体等。本文研究发现张敏（1998）的观点，即双向领属为“的”字隐现的主因是可信的。虽然张敏认为人称代词与名词之间关系上的紧密程度并不影响“的”字隐现，但本文发现无论人称代词还是名词都存在认知上的“远”和“近”概念上的差异，且“的”字的隐现受此差异影响。此外，本研究结果也显示文体的差异也影响“的”字的使用，即非正式文体倾向于省略“的”，而正式文体则倾向于加“的”。There were various studies regarding the factors associated with the presence and absence of the function word 的 de. Zhang’s (1998) proposal from the perspective of cognitive linguistics has been widely recognized by different researchers. However, Zhang’s proposal was not supported with large amount of data. As such, this paper aims to verify his points with corpus data and statistical analysis. This study will mainly focus on possessive structures, which consists of personal pronoun (as the modifier), de (optional) and noun (as the head noun). Word lists of pronouns and nouns were constructed respectively to find out whether there is a discrepancy among different combinations of pronouns and nouns. This paper investigated multiple factors that may affect the presence of de, including pronouns and nouns, syllable number of nouns, lexical meanings of the nouns. In Zhang’s point of view, two-way possessive structure is the main reason for the absence of “de”, and our study results verified this point. Although Zhang assumes that the close connection of personal pronoun and noun is not a factor that affects the absence of “de”, our study finds that different pronouns and head nouns show different uses of de, and such difference can be ascribed to the concepts of “far” and “close” denoted in the pronouns and head nouns. In addition, this study shows that genre also affects the presence and absence of de: specifically, texts with informal language show a tendency to omit de, whereas texts with more formal language tend to use de.